(untitled) - Power, Mick (New York, NY, 2007)
The relationship between thinking and feeling has puzzled philosophers for centuries, but more recently has become a dominant focus in psychology and in the brain sciences. This second edition of the highly praised Cognition and Emotion examines everything from past philosophical to current psychological perspectives in order to offer a novel understanding of both normal emotional experience and the emotional disorders.
Keywords: Emotions and cognition,Cognitive psychology,Psychotherapy